Whats next in remote sensing archaeology? Use of field spectroscopy to design a new space sensor - Hadjimitsis, Diofantos G. (My University, 2014)
The traditional archaeological surveys have been shifted through time from single to multi-disciplinary studies of material remains based on the advantages of new technologies. Remote Sensing (RS) techniques in the last years have been proven to be an essential tool for the detection of un-excavated sites as well an important tool for the better understanding of the landscape of a site. Although the use of such technologies is widely accepted by the archaeological community, the practical use of these RS is not equally adopted. This phenomenon has been dramatically increased though the last years, and therefore "two-speed archaeology"? is more evidence than before: Archaeologists in technologically developed countries may fully exploit RS technologies while in following countries this is still limited due to the lack of funding or equipment (e.g. special RS airplanes). Despite the fact that the above phenomenon is also frequently observed in other scientific fields, when this comes to archaeology then the problem is of paramount importance for the science itself: how can we better understand human past and old civilizations -which goes beyond the geographical limits of modern countries- when the data quality is fragmental though out the world? Extensive field spectroscopy measurements contacted in simulated archaeological environments have identified spectral regions suitable for the detection of buried archaeological research. Such characteristics can be implemented into a specially designed satellite sensor in order to support archaeological research. The potential use of such sensor will be a break though for the science of archaeology. The sensor can fully exploit the advantages of space technology and therefore can be used to support archaeological surveys in pan-European level as well outside Europe. The sensor will be able to provide a better inside look to lost landscapes and archaeological remains and therefore providing to archaeologists new windows to their research. It is a time to design a full experimental study by combining field spectroscopy, UAV and other auxiliary tools such as sun-photometers for suggesting an ideal new space sensor for archaeology applications.
Keywords: Archaeology; Remote sensing archaeology; Satellite sensor; Space; Spectroscopy; UAV